(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Exposure to radiation and/or batteries containing lead/cadmium, is currently under huge investigations as they are causing many health problems. The aim of this study is to evaluate the effect of radiation and toxicity of lead and cadmium on hematological cells. Methods: Forty subjects who previously exposed to lead/cadmium, twenty five radiologist and 10 healthy controls were recruited to this study. This study was conducted between January 2017 - April 2017 in Riyadh city, KSA. A questionnaire was distributed and answers were taken by the interviewer. Ten ml of whole blood in EDTA tube were collected and immediately tested by Abbott Cell Hematology Analyzer. Results: There was a significant difference in Hgb levels between batteries exposed people and healthy controls. Also there was a significant increase on WBCs count and lymphocytes count on battery exposed people compared to controls and radiologist. Almost 43% of battery exposed people have allergic reactions compared to controls. Conclusion: Monitoring irradiation and lead/cadmium toxicity levels is suggested in patients with a high risk of immunocompraimised or chronic diseases patients. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.200-204